Knowledge Translation in Healthcare - Towards Understanding its True Complexities; Comment on "Using Complexity and Network Concepts to Inform Healthcare Knowledge Translation" - Joachim P. Sturmberg (Kerman University of Medical Sciences, 2018)
This commentary argues that to fully appreciate the complexities of knowledge transfer one firstly has to distinguish between the notions of "data, information, knowledge and wisdom," and that the latter two are highly context sensitive. In particular one has to understand knowledge as being personal rather than objective, and hence there is no form of knowledge that a-priori is more authoritative than another. Secondly, knowledge transfer in organisations can only be successful if the organisation is organised and managed as a "complex adaptive organisation" - its key characteristics arising from it's a-priori defined common "purpose, goals and values." Knowledge transfer, seen as "whole of system/organisation learning," is highly context sensitive; while the principles may apply to many organisations, knowledge as such is not transferable from one context to another, it always will be a unique learning exercise at this particular point in time in this particular organisation.